Induction gemcitabine in standard dose or prolonged low-dose with cisplatin followed by concurrent radiochemotherapy in locally advanced non-small cell lung cancer - Vrankar, Martina (Radiology and oncology (Ljubljana), 2014)
The optimal combination of chemotherapy with radiation therapy for treatment locally advanced non-small cell lung cancer (NSCLC) remains an open issue. This randomized phase II study compared gemcitabine in two different schedules and cisplatin - as induction chemotherapy, followed by radiation therapy concurrent with cisplatin and etoposid. Patients and methods. Eligible patients had microscopically confirmed inoperable non-metastatic non-small cell lung cancer; fulfilled the standard criteria for platin-based chemotherapy; and signed informed consent. Patients were treated with 3 cycles of induction chemotherapy with gemcitabine and cisplatin. Two different aplications of gemcitabine were compared: patients in arm A received gemcitabine at 1250 mg/m2 in a standard half hour i.v. infusion on days 1 and 8; patients in arm B received gemcitabine at 250 mg/m2 in prolonged 6-hours i.v. infusion on days 1 and 8. In both arms, cisplatin 75 mg/m2 on day 2 was administered. All patients continued treatment with radiation therapy with 60-66 Gy concurrent with cisplatin 50 mg/m2 on days 1, 8, 29 and 36 and etoposid 50 mg/m2 on days 1-5 and 29-33. The primary endpoint was response rate (RR) after induction chemotherapy; secondary endpoints were toxicity, progression-free survival (PFS) and overall survival (OS). Results. From September 2005 to November 2010, 106 patients were recruited to this study. No statistically signifficant differences were found in RR after induction chemotherapy between the two arms (48.1% and 57.4%, p = 0.34). Toxicity profile was comparable and mild with grade 3/4 neutropenia as primary toxicity in both arms. One patient in arm B suffered from acute peripheral ischemia grade 4 and an amputation of lower limb was needed. With a median follow-up of 69.3 months, progression-free survival and median survival in arm A were 15.7 and 24.8 months compared to 18.9 and 28.6 months in arm B. The figures for 1- and 3-year overall survival were 73.1% and 30.8% in arm A, and 81.5 % and 44.4% in arm B, respectively. Conclusions. Among the two cisplatin-based doublets of induction chemotherapy for inoperable NSCLC, both schedules of gemcitabine have a comparable toxicity profile. Figures for RR, PFS and OS are among the best reported in current literature. While there is a trend towards better efficacy of the treament with prolonged infusion of gemcitabine, the difference between the two arms did not reach statistical significance
Keywords: gemicitabin; induction chemotherapy; kemoterapija; nedrobnocelični rak; non-small cell lung cancer; pljučni rak; radiation therapy; randomized clinical trial